Brazilian pulmonology guidelines on Delphi panel for post-coronavirus disease 2019 - Tanni, Suzana Erico [UNESP]; Baldi, Bruno Guedes; Godoy, Irma [UNESP]; Bacha, Hélio Arthur; Barbosa, Alexandre Naime [UNESP]; Bernardo, Wanderley Marques (FapUNIFESP (SciELO), 2023)
he Guidelines Project, an initiative of the Brazilian Medical Association, aims to combine information from the medical field to standardize how to conduct, and to assist in the reasoning and decision-making of doctors. The information provided by this project must be critically evaluated by the physician responsible for the conduct that will be adopted, depending on the conditions and the clinical condition of each patient.